2016
DOI: 10.5539/ies.v9n7p130
|View full text |Cite
|
Sign up to set email alerts
|

Will Medical Technology Deskill Doctors?

Abstract: This paper discusses the impact of medical technology on health care in light of the fact that doctors are becoming more reliant on technology for obtaining patient information, making diagnoses and in carrying out treatments. Evidence has shown that technology can negatively affect doctor-patient communications, physical examination skills, and development of clinical knowledge. We propose three possible approaches to medical education and professional development to assist human doctors in acquiring a better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
0
19
0
3
Order By: Relevance
“…As a final note, we believe that technology should facilitate the delivery of care without negatively affecting doctor-patient communications, physical examination skills, the perception of safety and security among patients, and the development of clinical knowledge. 15 A potential side effect of the increased usage of technology in healthcare is the rise in costs that may hamper the overall accessibility of cure and care services, both from a patient and a professional perspective. Indeed, since clinicians are becoming more dependent on technology, in particular for accessing patient information, reaching diagnoses and delivering care, undergraduate and professional development training on using medical technology in the domains of cure and care has become a must to ensure autonomy while interfacing with medical technology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a final note, we believe that technology should facilitate the delivery of care without negatively affecting doctor-patient communications, physical examination skills, the perception of safety and security among patients, and the development of clinical knowledge. 15 A potential side effect of the increased usage of technology in healthcare is the rise in costs that may hamper the overall accessibility of cure and care services, both from a patient and a professional perspective. Indeed, since clinicians are becoming more dependent on technology, in particular for accessing patient information, reaching diagnoses and delivering care, undergraduate and professional development training on using medical technology in the domains of cure and care has become a must to ensure autonomy while interfacing with medical technology.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, since clinicians are becoming more dependent on technology, in particular for accessing patient information, reaching diagnoses and delivering care, undergraduate and professional development training on using medical technology in the domains of cure and care has become a must to ensure autonomy while interfacing with medical technology. 15 …”
Section: Resultsmentioning
confidence: 99%
“…The primacy of technological assessment may also affect examination skills as physicians lose the nuance of unique patient histories and subjugate informed decision making to technology-dependent reasoning. 30 …”
Section: Safety and Quality Issues In Ai Usementioning
confidence: 99%
“…Research on the overreliance of technology in medicine has found that the increased use of EHRs has led to a prioritization of physician-technology interactions over physician-patient interactions, leading to decreased patient satisfaction, a scenario that could foreshadow the role of AI in patient care. 30 Patients also deserve to be informed of the use of AI in clinical care. The failure to disclose the use of AI tools to patients may diminish the trust between patients and clinicians.…”
Section: Safety and Quality Issues In Ai Usementioning
confidence: 99%
“…Especially in the context of care, the usage of technologies without a detailed understanding of the machine learning process that leads to clinical outcomes can determine some obstacles to professional practice: (1) Employing the marketing strategy would promote a medical/ technological culture according to which the best tools are those you can use without asking questions; in other words, reducing doctors' critical thinking on the resources they use on a daily basis. Secondarily, the promotion of a medical culture in which technologies can be used as "black boxes" can lead to overconfidence in doctors (i.e., relying on technology for tasks other than those it was originally designed to perform) and to deskilling (i.e., reducing user's abilities because activities can now be performed by machines; [24,25]). In such a scenario, doctors would not be able to intervene effectively when AI does not work or is under maintenance.…”
mentioning
confidence: 99%